Dilepton Spectroscopy of QCD Matter at Collider Energies - Ralf Rapp (Advances in High Energy Physics)
Low-mass dilepton spectra as measured in high-energy heavy-ion collisions are a unique tool to obtain spectroscopic information about the strongly interacting medium produced in these reactions. Specifically, in-medium modifications of the vector spectral function, which is well known in the vacuum, can be deduced from the thermal radiation off the expanding QCD fireball. This, in particular, allows to investigate the fate of the ρ resonance in the dense medium and possibly infer from it signatures of the (partial) restoration of chiral symmetry, which is spontaneously broken in the QCD vacuum. After briefly reviewing calculations of thermal dilepton emission rates from hot QCD matter, utilizing effective hadronic theory, lattice QCD, or resummed perturbative QCD, we focus on applications to dilepton spectra at heavy-ion collider experiments at RHIC and LHC. This includes invariant-mass spectra at full RHIC energy with transverse-momentum dependencies and azimuthal asymmetries, as well as a systematic investigation of the excitation function down to fixed-target energies, thus making contact to previous precision measurements at the SPS. Furthermore, predictions for the energy frontier at the LHC are presented in both dielectron and dimuon channels.